2021
DOI: 10.26508/lsa.202101159
|View full text |Cite
|
Sign up to set email alerts
|

Elevated glucose increases genomic instability by inhibiting nucleotide excision repair

Abstract: We investigated potential mechanisms by which elevated glucose may promote genomic instability. Gene expression studies, protein measurements, mass spectroscopic analyses, and functional assays revealed that elevated glucose inhibited the nucleotide excision repair (NER) pathway, promoted DNA strand breaks, and increased levels of the DNA glycation adduct N2-(1-carboxyethyl)-2ʹ-deoxyguanosine (CEdG). Glycation stress in NER-competent cells yielded single-strand breaks accompanied by ATR activation, γH2AX induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…HIF-1α modification by MG decreases heterodimer formation and promoter binding . This is a potential mechanism for the decreased DNA repair protein expression in cells grown in high glucose observed by Ciminera et al as DNA repair proteins are targets for HIF-1α transcription activity . Recently, work from Marnett demonstrated that histones are targets for MG modification, potentially regulating gene expression .…”
Section: Mg-protein Adducts: Formation and Impact On Structure And Fu...mentioning
confidence: 95%
See 4 more Smart Citations
“…HIF-1α modification by MG decreases heterodimer formation and promoter binding . This is a potential mechanism for the decreased DNA repair protein expression in cells grown in high glucose observed by Ciminera et al as DNA repair proteins are targets for HIF-1α transcription activity . Recently, work from Marnett demonstrated that histones are targets for MG modification, potentially regulating gene expression .…”
Section: Mg-protein Adducts: Formation and Impact On Structure And Fu...mentioning
confidence: 95%
“…Ciminera et al recently showed that high glucose decreased the expression of proteins in the NER pathway, leading to accumulation of MG-DNA adducts corresponding to decreased functional repair. 87 The authors suggested that high glucose may downregulate NER protein expression through a HIF-1α-dependent mechanism. 87 When cells are unable to efficiently repair DNA damage, it leads to persistent lesions that may cause genomic instability and mutations (Figure 4A).…”
Section: ■ Mg-ages On Dna and Proteinmentioning
confidence: 99%
See 3 more Smart Citations